Genetic engineering and stem cell therapy for the treatment of heart failure - Rajan, Silpa; Lalitha Madhavu, Minu (International Journal of Engineering and Technology, 2018)
Endogenous cardiac stem cells (eCSCSs) are defined as tissue specific progenitor cells concealed within human heart. Adult heart was thought primarily as a post mitotic organ devoid of any regenerative capacity. But eCSCSs proves the existence of immature cycling myo-cytes in adult myocardium which promotes regeneration after infarction. In addition to the restocking ofheart tissue, eCSCs put up in turn marks major and paramount role in growth and development of heart tissue.Myocardial infarction has become a major cause of death of a very large population per year and those who outlast live with heart stoppage. The permanent dropping of cardiomyocytes at the time of infarction makes a healthy body susceptible to irregular heartbeat called arrhythmia as electro-mechanically dysfunctional tissues are fabricated. Under this condition, heart becomes unable to pump sufficient amount of blood to the body including heart, lungs, brain leading to cardiovascular collapse. Brain and other organs can’t work properly and may shut down or will be damaged when heart doesn't pump blood productively. Due to arrhythmia, as heart doesn’t pump blood effectively to various vital organs of the body, they can't function properly and eventually wear off. To reinstate cardiac function in heart failure, potential therapeutic approaches via cell based therapies using multipotent (adult) and pluripotent (embryonic) stem cells are used.
Keywords: Arrhythmia; Embryonic Cardiac Stem Cells (ECSCSS); Heart Failure (HF); Myocardial Infarction (MI); Multipotent and Pluripotent Stem Cells.